2015
DOI: 10.1089/jir.2014.0125
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD138-Targeted Interferon Is a Potent Therapeutic Against Multiple Myeloma

Abstract: Multiple myeloma (MM), a plasma cell malignancy, is the second most prevalent hematologic malignancy in the US. Although much effort has been made trying to understand the etiology and the complexities of this disease with the hope of developing effective therapies, MM remains incurable at this time. Because of their antiproliferative and proapoptotic activities, interferons (IFNs) have been used to treat various malignancies, including MM. Although some success has been observed, the inherent toxicities of IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…27,28 Previous studies in our laboratory [8][9][10][11] have shown that genetic fusion of IFNs to an antibody is an effective strategy to specifically target IFN to the tumor microenvironment, reduce systemic toxicity, and increase half-life.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27,28 Previous studies in our laboratory [8][9][10][11] have shown that genetic fusion of IFNs to an antibody is an effective strategy to specifically target IFN to the tumor microenvironment, reduce systemic toxicity, and increase half-life.…”
Section: Discussionmentioning
confidence: 99%
“…25 We have shown previously that targeting IFNa and IFNb fusion proteins is an effective strategy against lymphoma and MM. [8][9][10][11] Based on these studies, we initiated Phase 1 clinical testing of anti-CD20-IFNa to treat B-cell lymphomas (Clinical Trials.gov Identifier NCT02519270), underscoring the therapeutic potential of this approach. One of the goals of the study described here was to determine the effect of combining treatment using IFN fusion proteins with the FDA-approved drug, bortezomib.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations